PRINCIPLES OF HONESTY IN GOOD FAITH BUYING LAND - Dwi Atmoko (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The land sale and purchase agreement does not rule out the possibility of a third party claiming that the land is his. Land issues often lead to long-term conflicts between communities and between communities and legal entities. Controversy about this land seems to be endless and always happens in this world, because human demand for land always increases along with population growth. In this study the author is interested in researching about how the application of the principle of good faith in the sale and purchase agreement of land? The type of research used is normative juridical and empirical juridical. The results of the study stated that the application of the principle of good faith in the sale and purchase agreement of an agreement. The parties who make the sale and purchase should adhere to the principle of good faith because the principle of good faith is very important in anticipating and minimizing buying and selling disputes. Because in this house sale there is a preliminary agreement that precedes the actual Sale and Purchase Agreement, then the PPJB still has binding power based on honesty.